Multimodal imaging analysis of retinal and choroidal microvascular abnormalities in a case of ocular decompression sickness - Christine Clavell; James Dossett; Sanya Yadav; Ami Patel; L. Carol Laxson; Ghassan Ghorayeb (American Journal of Ophthalmology Case Reports)
Purpose: Decompression sickness can result in a variety of ocular manifestations due to barotrauma. The retinal complications of this illness are less defined. In this case report, we describe a case of pigment epithelial detachment (PED) with retinal and choroidal microvasculature changes secondary to ocular decompression sickness in a scuba diver. Observations: The parafoveal serous pigment epithelial detachment resulted in a scotoma associated with a kaleidoscope-like visual disturbance and mildly decreased vision which started immediately after the accident. Multimodal imaging was obtained revealing a serous PED without exudation, pooling of dye on fluorescein angiography, and decreased flow signal on optical coherence tomography angiography (OCT-A) in the deep capillary plexus and choriocapillaris in the area of the PED. Over the course of three months, the serous PED spontaneously resolved leaving behind subtle retinal pigment epithelium (RPE) alterations. Visual acuity also improved over the same time period however the visual disturbance had not completely resolved at the date of last follow-up. Conclusions and importance: The imaging findings, temporal association with the diving accident, and short timeframe to resolution of this PED favor an etiology related to ocular decompression sickness. PED formation in this context may be secondary to 1) RPE dysfunction due to endothelial cell damage from free radicals and 2) choroidal ischemia resulting from gas emboli. To our knowledge, this is the first reported case where OCT-A has been used to demonstrate choroidal ischemia in ocular decompression sickness. The patient received hyperbaric oxygen treatments for several weeks following the accident which may have contributed to the rapid resolution of the PED supporting the role of choroidal ischemia in its pathogenesis.